Promoting intestinal antimicrobial defense and microbiome symbiosis contributes to IL-22-mediated protection against alcoholic hepatitis in mice - Yue, Ruichao; Wei, Xiaoyuan; Hao, Liuyi; Dong, Haibo; Guo, Wei; Sun, Xinguo; Zhao, Jiangchao; Zhou, Zhanxiang; Zhong, Wei (Frontiers in Immunology, 2023)
Background The hepatoprotective effect of interleukin 22 (IL-22) has been reported in several models of liver injuries, including alcohol-associated liver disease (ALD). However, the intestinal role of IL-22 in alcoholic hepatitis remains to be elucidated. Methods Intestinal IL-22 levels were measured in mice fed with alcohol for 8 weeks. IL-22 was then administered to alcohol-fed mice to test its protective effects on alleviating alcoholic hepatitis, focusing on intestinal protection. Acute IL-22 treatment was conducted in mice to further explore the link between IL-22 and the induction of antimicrobial peptide (AMP). Intestinal epithelial cell-specific knockout of signal transducer and activator of transcription 3 (STAT3) mice were generated and used for organoid study to explore its role in IL-22-mediated AMP expression and gut barrier integrity. Results After alcohol feeding for 8 weeks, the intestinal levels of IL-22 were significantly reduced in mice. IL-22 treatment to alcohol-fed mice mitigated liver injury as indicated by normalized serum transaminase levels, improved liver histology, reduced lipid accumulation, and attenuated inflammation. In the intestine, alcohol-reduced Reg3γ and α-defensins levels were reversed by IL-22 treatment. IL-22 also improved gut barrier integrity and decreased endotoxemia in alcohol-fed mice. While alcohol feeding significantly reduced Akkermansia, IL-22 administration dramatically expanded this commensal bacterium in mice. Regardless of alcohol, acute IL-22 treatment induced a fast and robust induction of intestinal AMPs and STAT3 activation. By using in vitro cultured intestinal organoids isolated from WT mice and mice deficient in intestinal epithelial-STAT3, we further demonstrated that STAT3 is required for IL-22-mediated AMP expression. In addition, IL-22 also regulates intestinal epithelium differentiation as indicated by direct regulation of sodium-hydrogen exchanger 3 via STAT3. Conclusion Our study suggests that IL-22 not only targets the liver but also benefits the intestine in many aspects. The intestinal effects of IL-22 include regulating AMP expression, microbiota, and gut barrier function that is pivotal in ameliorating alcohol induced translocation of gut-derived bacterial pathogens and liver inflammation.